Audit Sampling Untuk Pengujian Pengendalian dan Pengujian Substantif Atas Transakasi - Andini, Nisha (CV. Pusdikra Mitra Jaya, 2025)
Auditors strive to obtain a representative sample when selecting a sample from a population because the items selected from the population are similar to those selected from the population. A representative sample, also called a representative sample, is a sample whose characteristics are nearly identical to those of the population, so that the items taken from the population are similar to those taken from the population. However, in practice, auditors never know whether the sample is representative. This type of research is qualitative descriptive research that focuses on available sources of information about the strength of data analysis. These sources come from various books and publications that discuss existing theories clearly and comprehensively to create text in the form of articles. In practice, auditors cannot know whether a sample is representative or not, even after all testing has been completed. However, auditors can increase the likelihood of a sample being representative by carrying out audit sampling steps correctly. The steps in audit sampling are planning the sample, selecting the sample, conducting the test, and evaluating the results. Two things that can cause sample results to be unrepresentative are nonsampling errors and sampling errors. The purpose of auditing in selecting a sample from a population is to obtain a representative sample. A representative sample is a sample that has the same characteristics as the population. This means that the population items included in the sample are the same as the items not included in the sample.